Priset på åkermark - Lundell, Anders; Östlund, Jonas (2010)
The price of farmland has risen sharply in the last 20 years. This has led to discussions about what creates the value of farmland. The aim in this study was to try and find what factors are affecting the price on farmland. The area that is studied is the counties around Mälardalen during the period 2005 to 2009.